Novel surgical technique for management of tongue schwannoma: case report - Jain, Neha; Shishodia, Shama; Dham, Ruchima; Roy, Suparna; Goel, Sachin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Schwannomas are rare, solitary, slow growing, smooth surfaced and well encapsulated tumors. Schwannomas of head and neck region account for 25-40% of all the cases. Approximately 1%–12% of schwannomas occur intraorally, the tongue being the most common site. Complete surgical excision is the treatment of choice. In this article, we describe a case of tongue schwannoma in a child, along with diagnostic and treatment options of tongue lesions. The tongue mass was completely excised via trans-oral approach using coblation method. The patient followed up for 1 year; he had an uneventful recovery and no recurrence.